Simulação e análise de uma coluna de esgotamento para remoção de cloro de corrente aquosa utilizando técnicas de planejamento experimental - Sousa , Victor Cesar Pugliesi de (2017)
The objective of this work was to simulate, analyze and optimize a real column of chlorine removal in the aqueous stream. This column is composed by 3 equilibrium stages, two stages containing 3 meters of Tri-pack 1” package in each one and the third one referring to the bottom of the column. The column operates at atmospheric pressure and uses saturated steam to remove the chlorine present in the water. The wastewater consisting of saturated water with chlorine (chlorinated water) pass through a process of heat exchange with the dechlorinated water stream arising from the column bottom, after that, the chlorinated water stream gets in by the top of the column. Saturated steam is introduced from the bottom of the column in countercurrent with chlorinated water to raise the temperature inside the column and facilitate the release of the chlorine gas into the chlorinated water. In addition of that, a stream of hydrochloric acid also enters by the top of the column to increase the amount of chlorine ions and favors the formation of chlorine gas and makes it difficult to form impurities such as hypochlorous acid. The simulation of this unit was performed in Aspen Plus® and the computational experiments were performed following a complete experimental design 24. The STATISTICA® software was used to perform the statistical analysis of the results of the simulations, to evaluate the main effects and interaction effects between the factors and generate a metamodel that describes the process. The selected factors for this work were: hydrochloric acid flow, steam flow, chlorinated water stream flow rate and package type. Analyzing the studied packages by the statistical results, it was observed that both of them, Tri-pack and Intalox saddles, do not have significant effects on the process, while hydrochloric acid flow, steam flow and chlorinated water flow were significant as the interactions between hydrochloric acid flow and chlorinated water flow and the interactions between hydrochloric acid flow and steam flow. Thus, a 3³ experimental design was performed using the significant factors in the experimental planning 24 as variables, to observe possible peaks in the worked interval of the variables. Through this work, it was possible to define that the significant factors were, in descending order: steam flow, chlorinated water flow and hydrochloric acid flow. In addition, the interactions between chlorinated water flow and vapor flow and between steam flow and hydrochloric acid flow.